Selective union of ATP vs ADP to an amino/amide macrocycle and its Cu2+ complexes: potentiometric, spectrophotometric and theoretical approximations - Armando Ferrer Serrano; Yennys Hernández Molina (The Journal of Engineering and Exact Sciences)
The protonation equilibria of a new amine/amide type macrocycle and its complexation with Cu(II) in solution have been studied by potentiometry and UV-Visible Spectrophotometry. The ligand shows four protonation constants and one unusual deprotonation constant. Six mononuclear and four binuclear copper II complexes were found and reported its stability constant values. Some species predominate in specific ranges of pH, which might be important for biomimetic studies. It was found that the studied ligand forms stable mononuclear and binuclear complexes with Cu (II) and these species have similar geometries, squared pyramid, above pH 7. An evaluation through its potentiometrically determined stability constants of the selective recognition of ATP over ADP by this macrocycle and its Cu (II) complexes is presented. With or without the presence of Cu (II) ions, the ligand forms more stable complexes with ATP over ADP, the stability of these species increase with pH. Both, the stability quotients and the species distribution diagrams for the ATP-ADP mixed systems shows the inclination of the studied systems to selectively bind ATP over ADP, so, in principle, they can be used for the selective recognition of ATP or as catalysts in the hydrolysis of this nucleotide.